Strategy for Overcoming Population Growth Problems in Japan - Respatiadi, Faisal; Jalaluddin, Muzani; Munandar, Aris (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
Japan is considered a developed country with an economy that is growing strongly from year to year. Even though Japan is currently a "developed" country, it does not mean that Japan is without problems. Currently, Japan's problem is the decline in the number of births in Japan. It's not new, but it's been around since 1975. The phenomenon of declining birth rates in Japan is known as shoushika. Shoushika phenomenon is a decline in the child population in Japan, this phenomenon is inseparable from the decline in birth rates and the rapid growth of the elderly population. Judging from the historical factors that after World War II, Japan built the country from adversity with the hard work of its people and made Japan a developed country. But the effect of its focus on development makes Japanese society individualistic. So it is not surprising that the Shoushika phenomenon emerged and turned Japan into a demographic crisis. Japan is experiencing a population decline due to a declining birth rate. In addition, the number of seniors (elderly) and older people over 65 is increasing. The phenomenon is predicted to continue in the future, the ratio of old to young is one in four.